Electronic health record-wide association study for atrial fibrillation in a British cohort - Chung, Sheng-Chia; Schmit, Amand F.; Lip, Gregory Y. H.; Providencia, Rui (Frontiers in Cardiovascular Medicine, 2023)
Background Atrial fibrillation (AF) confers a major healthcare burden from hospitalisations and AF-related complications, such as stroke and heart failure. We performed an electronic health records-wide association study to identify the most frequent reasons for healthcare utilization, pre and post new-onset AF. Methods Prospective cohort study with the linked electronic health records of 5.6 million patients in the United Kingdom Clinical Practice Research Datalink (1998–2016). A cohort study with AF patients and their age-and sex matched controls was implemented to compare the top 100 reasons of frequent hospitalisation and primary consultation. Results Of the 199,433 patients who developed AF, we found the most frequent healthcare interactions to be cardiac, cerebrovascular and peripheral-vascular conditions, both prior to AF diagnosis (41/100 conditions in secondary care, such as cerebral infarction and valve diseases; and 33/100 conditions in primary care), and subsequently (47/100 conditions hospital care and 48 conditions in primary care). There was a high representation of repeated visits for cancer and infection affecting multiple organ systems. We identified 10 novel conditions which have not yet been associated with AF: folic acid deficiency, pancytopenia, idiopathic thrombocytopenic purpura, seborrheic dermatitis, lymphoedema, angioedema, laryngopharyngeal reflux, rib fracture, haemorrhagic gastritis, inflammatory polyneuropathies. Conclusion Our nationwide data provide knowledge and better understanding of the clinical needs of AF patients suggesting: (i) groups at higher risk of AF, where screening may be more cost-effective, and (ii) potential complications developing following new-onset AF that can be prevented through implementation of comprehensive integrated care management and more personalised, tailored treatment. Clinical trial registration NCT04786366